A Minimal Avian Retroviral Packaging Sequence Has a Complex Structure - Banks, Jennifer D. (American Society for Microbiology, 1998)
We have defined a 160-nucleotide region, Mψ, from the 5′ leader region of the Rous sarcoma virus genome that is sufficient to direct the packaging of a heterologous RNA. Mψ contains the putative O3 stem structure that has previously been shown, and that has been confirmed in this study, to be important for the efficient packaging of avian leukosis-sarcoma virus RNA. Analyses of several O3 stem mutants revealed that other regions within Mψ can interfere with the proper folding of altered sequences which are predicted to form a wild-type O3 stem.